Partial dollarization and financial frictions in emerging economies. Issue 2 (21st September 2022) - Gabriel, Vasco J.; Levine, Paul; Yang, Bo
Abstract: How do financial frictions affect macroeconomic volatility and monetary policy in emerging market economies? This article assesses the empirical relevance of such frictions by estimating a two‐bloc emerging market/rest‐of‐the‐world model containing two key features of emerging economies: partial transaction and liability dollarization, and financial frictions where capital financing is partially or totally in foreign currency. Our estimation employs the "one‐step approach" which allows us to be "agnostic" regarding nonstationarity in the data and simultaneously estimate structural and trend parameters. Using data for Peru and the US, we find substantial empirical support for both the financial accelerator and partial dollarization mechanisms. The data fit of the baseline model improves with the addition of each of these frictions, exogenous shocks are significantly amplified in their presence and our preferred model captures several important stylized facts of a small emerging open economy.